Working Conditions and Special Educators' Reading Instruction for Students With Emotional and Behavioral Disorders. (July 2021) - Mathews, Hannah Morris; Lillis, Jennifer L.; Bettini, Elizabeth; Peyton, David J.; Pua, Daisy; Oblath, Rachel; Jones, Nathan D.; Smith, Stephen W.; Sutton, Rachel
Working conditions may be an important lever to support special educators' reading instruction for students with emotional and behavioral disorders (EBD). Thus, we explored how working conditions relate to the quality of special educators' reading instruction in upper-elementary, self-contained classes for students with EBD. Using mixed methods to examine video observations of reading instruction and varied data sources on working conditions, we found that special educators who provided stronger instruction had a partner coleading their program, and consistent paraprofessionals, with time and support for training. Partners and paraprofessionals, together, protected special educators' instruction time. Other conditions (i.e., material resources, role differentiation, role conceptions, planning time) emerged as potentially important, but evidence was less robust. Results indicate partners and paraprofessionals may be important forms of collegial support. These findings have important implications for improving the quality of instruction in self-contained settings for students with EBD.